The situation of women in the Polish labour market in the light of changes in the pension security system - Gawrycka, Małgorzata; Nikulin, Dagmara (Research Papers of Wrocław University of Economics, 2018)
The aim of the study is to examine the opinion of a group of women on their economic activity and decisions related to retirement. The first part of the article reviews previous research related to the economic activity of older people with a special focus on women. In the empirical part of the article, women’s opinions on issues related to retirement were analyzed. The research was carried out in 2016 on a sample of 45 women, which is a non-representative sample selection technique. The method used is similar to the method of “random choice” or “convenience choice” (convenience sampling). Research results indicate that retirement was often not fully voluntary, and resulted from the liquidation of the workplace or from the bad atmosphere
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 509, s. 70-83
Keywords: women retirement; labour market; Poland; activity of women; kobiety na emeryturze; rynek pracy; aktywność zawodowa